Criminal Legal Protection of the Forest: History and Modernity - Tovsultanov R. A.; Tovsultanova M. Sh.; Galimova L. N. (SHS Web of Conferences, 2023)
The purpose of this scientific article is to consider the specifics of development, some improvement of the modern reflection of the criminal law protection of the forest in the domestic criminal legislation.The following methods were used in the work: dialectical, logical, formal-legal, comparative-historical and many others.On the basis of the study, it is stated that it is the indication of the “damage” caused by the offenses we are considering that serves as a fundamental criterion for distinguishing crimes from related acts. Since otherwise, as it was before the recent change in Art. 261 of the Criminal Code of the Russian Federation, for law enforcement agencies there was a problem of clearly distinguishing the nature of the unlawful act committed by the guilty person.The domestic legislator is pointed out the need to analyze the correctness of his definition of the object applicable to the act reflected in Art. 191 of the Criminal Code of the Russian Federation.